2015
DOI: 10.1002/glia.22833
|View full text |Cite
|
Sign up to set email alerts
|

Different danger signals differently impact on microglial proliferation through alterations of ATP release and extracellular metabolism

Abstract: Microglia rely on their ability to proliferate in the brain parenchyma to sustain brain innate immunity and participate in the reaction to brain damage. We now studied the influence of different danger signals activating microglia, both internal (typified by glutamate, associated with brain damage) and external (using a bacterial lipopolysaccharide, LPS), on the proliferation of microglia cells. We found that LPS (100 ng/mL) increased, whereas glutamate (0.5 mM) decreased proliferation. Notably, LPS decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 53 publications
4
44
2
Order By: Relevance
“…This is consistent with the finding that microglia have no effect on epileptogenesis in hippocampal cultures . However, our results are inconsistent with reports showing that ATP and adenosine affect microglia activation and migration . Matyash et al .…”
Section: Discussionsupporting
confidence: 74%
“…This is consistent with the finding that microglia have no effect on epileptogenesis in hippocampal cultures . However, our results are inconsistent with reports showing that ATP and adenosine affect microglia activation and migration . Matyash et al .…”
Section: Discussionsupporting
confidence: 74%
“…This rise was undetectable in the presence of BMN or BMDM, but (at least in part) reversible by the co-administration of ARL67156. Thus, our findings are in line with that of George and colleagues46, and suggest a contribution of CD39 to the meningitis-associated decrease in CSF ATP.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, George and colleagues46 demonstrated that E. coli LPS can increase the extracellular catabolism of ATP into adenosine through ectonucleotidases by cultured microglial cells. In order to evaluate whether locally present immune cells contribute to the drop of CSF ATP levels in PM, we next cultured live S. pneumoniae in the absence or presence of murine BMN or BMDM in aCSF to which ATP was added at its physiological concentration24.…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant difference in the percentage of subventricular/ventricular zone at GD18, but did notice an effect at GD20, which may be related to LPS-induced gliosis or migration failure as discussed below. The alteration of cortex or cortical plate thickness may be due to the initial proliferation and activation of microglia, which subsequently decreases or returns to normal1256. Indeed, we found that microglia are activated in the presence of LPS (Fig.…”
Section: Discussionmentioning
confidence: 65%